Perubahan Jathil Obyog Di Dalam Kesenian Reyog Obyog Di Kota Ponorogo - Khrisna Wahyu Aditama; Octo Dendy Andriyanto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Jathil Obyog is a semi-oral folklore that is undergoing a process of change at this time. The purpose of this research is to find out the changes in Jathil Obyog in Reyog Obyog in Ponorogo City. This research is a qualitative research. There are three parts in this research, namely, the beginning of Jathil Obyog art in Ponorogo City, the change of Jathil Obyog art form in Ponorogo City, and the impact of Jathil Obyog art changes on the community. This research is a qualitative descriptive research. The data was obtained from interviews, observations and literature studies about Reyog Obyog. Data in the form of words and photos. The data is then analyzed through an intensive implementation process that is through a descriptive narrative which is then arranged in such a way and then produces the results of an in-depth analysis. The results of this research show that Jathil Obyog in the Reyog Obyog performance is a traditional performance art that comes from East Java, Indonesia and has gumathok elements. Jathil Obyog changed his mind. Starting from Dance Movements, Events, Makeup and Hair, Dance Properties, as well as Songs and Dances. For the general public, the intensity of Pagelaran Reyog Obyog is increasing, the public's interest in the art of Jathil Obyog is increasing, content creators are developing, and can develop and advance the UMKMe of the community. The intensity of the Reyog Obyog performance has a direct impact on the interests of the community.